2022
DOI: 10.1039/d1nr06119d
|View full text |Cite
|
Sign up to set email alerts
|

Stacking-dependent optical properties in bilayer WSe2

Abstract: The twist angle between the monolayers in van der Waals heterostructures provides a new degree of freedom in tuning material properties. We compare the optical properties of WSe2 homobilayers with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 46 publications
3
23
0
Order By: Relevance
“…However, when the incident laser resonantly excited the A exciton (1.63 and 1.65 eV data), contrast between the domains clearly emerges. [ 46 ] In accordance to previous theoretical calculations, [ 53 ] the breaking of inversion symmetry in the 3R‐bilayer leads to additional splitting of the valance band maximum around K points, which further results in split exciton resonances. Thus, correlating these complementary nonlinear optical imaging modalities allows us to unambiguously establish the crystal‐symmetry‐based origins of the contrast in local optical response.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…However, when the incident laser resonantly excited the A exciton (1.63 and 1.65 eV data), contrast between the domains clearly emerges. [ 46 ] In accordance to previous theoretical calculations, [ 53 ] the breaking of inversion symmetry in the 3R‐bilayer leads to additional splitting of the valance band maximum around K points, which further results in split exciton resonances. Thus, correlating these complementary nonlinear optical imaging modalities allows us to unambiguously establish the crystal‐symmetry‐based origins of the contrast in local optical response.…”
Section: Resultssupporting
confidence: 86%
“…The flake of interest includes both monolayer and bilayer regions. The dark‐colored bilayer region has a jigsaw‐like pattern, which is formed by multiple triangular domains with 3R and 2H stacking order, [ 46 ] as confirmed below using both nonlinear nano‐SHG and linear scattering scanning nearfield optical microscopy (s‐SNOM). AFM topography of the boxed area is shown in Figure 3b, where the bilayer and monolayer regions can be clearly distinguished by height.…”
Section: Resultsmentioning
confidence: 89%
“…Raman spectroscopy is a nondestructive optical technique often used to provide a fingerprint of 2D materials systems, identifying the number of layers as well as providing insights into defect densities and interlayer interactions. , Recently, Raman spectroscopy has been used to identify phonon modes associated with moiré superlattices in twisted bilayers of MoS 2 and WS 2 and stacking-dependent behavior in homobilayers of WSe 2 , demonstrating that it is a powerful tool for probing systems that are sensitive to interlayer twist. In particular, Quan et al have also shown that small changes in twist angle in bilayer MoS 2 can lead to pronounced shifts in the frequencies of acoustic phonons, while the Raman-active optical phonon frequencies are only weakly dependent on twist angle .…”
Section: Introductionmentioning
confidence: 99%
“…The second-order nonlinear optical property modulation and GBs were revealed by SHG measurements. It was also known that the twisted angle or stacking order had an impact on some other optical properties of WSe 2 . The modulation effect of other light–WSe 2 interactions were observed in the homogeneous polycrystalline stacked WSe 2 material system.…”
Section: Resultsmentioning
confidence: 95%
“…Their optical properties were evidently affected by the layer numbers and the stacking orders. It was reported that the optical responses of second-harmonic generation (SHG) and Raman scattering were strongly dependent on layer number and stacking orders of TMDC materials. Therefore, those TMDC material systems with many quasi-periodic microstructures are useful for changing optical responses, thus modulating light–TMDC interactions. In this regard, polycrystalline TMDCs with many lattice imperfections of grain boundaries (GBs) provide an opportunity to construct a plethora of those microstructures in a crystal .…”
Section: Introductionmentioning
confidence: 99%